The Precautionary Principle in the Context of Mobile Phone and Base Station Radiofrequency Exposures - Dolan, Mike (National Institute of Environmental Health Sciences, 2009)
BACKGROUND: No health hazard has been established from exposure to radiofrequency fields up to the levels recommended by the International Commission on Non-Ionizing Radiation Protection. However, in response to public concern and the perceived level of scientific uncertainty, there are continuing calls for the application of the precautionary principle to radiofrequency exposures from mobile phones and base stations. OBJECTIVE: We examined the international evolution of calls for precautionary measures in relation to mobile phones and base stations, with particular focus on Australia and the United Kingdom. RESULTS: The precautionary principle is difficult to define, and there is no widespread agreement as to how it should be implemented. However, there is a strong argument that precautionary measures should not be implemented in the absence of reliable scientific data and logical reasoning pointing to a possible health hazard. There is also experimental evidence that precautionary advice may increase public concern. CONCLUSION: We argue that conservative exposure standards, technical features that minimize unnecessary exposures, ongoing research, regular review of standards, and availability of consumer information make mobile communications inherently precautionary. Commonsense measures can be adopted by individuals, governments, and industry to address public concern while ensuring that mobile networks are developed for the benefit of society.